PENGARUH JENIS KELAMIN, IPK, DAN SEMESTER TERHADAP LITERASI KEUANGAN MAHASISWA PRODI S1 EKONOMI PEMBANGUNAN UNIVERSITAS NEGERI MALANG - Wijayanti *; Grisvia Agustin; Farida Rahmawati (Universitas Negeri Malang, 2016)
Recently, financial literacy has became everyone’s compulsory need in managing as well as devising their finance. This research aims to know (1) How do gender, GPA, and semester influence financial literacy of sarjana’s degree students partially? (2) How do gender, GPA, and semester influence financial literacy of sarjana’s degree students simultaneously? This research used descriptive quantitative approach. The population is sarjana’s degree students of Development Economic in Universitas Negeri Malang on 2011-2014 generation. Furthermore, the sample of this research is 118 respondents from 2011 to 2014 generation by using quota sampling techniques. The data is collected by using questionnaires in which has been examined through validity and reliability test. Research’s results are: (1) Gender has positive and significant impacts to financial literacy of sarjana’s degree students, (2) GPA has positive and significant impacts to financial literacy of sarjana’s degree students, (3) Student’s semester has positive and significant impacts to financial literacy of sarjana’s degree students, (4) Gender, GPA, and student’s semester have positive and significant impacts to financial literacy of sarjana’s degree students simultaneously. The researcher suggests that next researcher may add other independent variables, which is related to financial literacy, so that the research would be more advanced.Keywords: Financial literacy, Gender, GPA, Semester